Advanced geotechnical engineering : soil-structure interaction using computer and material models - Desai, C. S. (Chandrakant S.), 1936-; Zaman, Musharraf (Boca Raton, [Florida] : CRC Press/Taylor & Francis, 2014)
'This book provides readers with a comprehensive treatment of computer methods so that they can use them for teaching, research, and solution of a wide range of practical problems in geotechnical engineering. It discusses factors such as in-situ conditions, elastic, plastic and creep deformations, stress path, volume change, existence of fluids (water), non-homogeneities, inherent and induced discontinuities leading to softening and failure, healing or strengthening, and type of loading'--
Includes bibliographical references and index.
Keywords: Soil-structure interaction